Postoperative radiotherapy improves survival in completely resected non-small cell lung cancer with pathologic N2 stage IIIA and positive lymph node count greater than one: a SEER-based retrospective cohort study - Diyang Zhu; Yuanyuan Xiao; Yuanyuan Xiao; Shancheng He; Shancheng He; Baochang Xie; Baochang Xie; Wenqi Zhao; Wenqi Zhao; Yuhui Xu (Frontiers in Surgery)
ObjectiveNon-small cell lung cancer (NSCLC) constitutes approximately 85% of lung cancer cases, with 20%–30% of patients diagnosed at stage III. While multimodal therapy is the standard for treating locally advanced NSCLC, the role of PORT remains controversial. This study seeks to evaluate the effect of postoperative radiotherapy (PORT) on overall survival (OS) and cancer-specific survival (CSS) in patients with resected pathologic N2 (pN2) stage IIIA NSCLC.MethodsData from the Surveillance, Epidemiology, and End Results Program (SEER) 17 registry (2010–2019) were analyzed. The cohort included 1,471 patients aged 65 years or older, diagnosed with stage IIIA pN2 NSCLC, who had undergone lobectomy or total pneumonectomy. Patients who had received neoadjuvant chemotherapy or radiotherapy were excluded. Univariate and multivariate analyses were conducted to assess the association of PORT with OS and CSS. Kaplan-Meier survival curves were employed to estimate survival outcomes, while the COX proportional hazards model was utilized for comparative analysis. PLN counts were stratified into two categories: ≤1 and >1.ResultsAmong the 1,471 patients included in the study, 613 (41.67%) received PORT, while 858 (58.33%) did not. PORT was associated with a significantly higher 1- and 3-year OS (89.96% and 68.49%, respectively) compared to the non-PORT group (87.44% and 61.88%, respectively, P = 0.03). However, no significant difference in CSS was observed between the groups (P = 0.15). Among patients with PLN counts >1, PORT significantly improved OS (HR = 1.32, 95% CI = 1.04–1.68, P = 0.0016) and CSS (HR = 1.32, 95% CI = 0.99–1.70, P = 0.026), whereas no significant differences were seen in patients with PLN counts ≤1.ConclusionsThis study underscores the potential of PORT in enhancing OS in patients with resectable pN2 stage IIIA NSCLC, particularly in those with PLN counts exceeding one. These findings suggest that PORT may offer improved outcomes in patients with extensive lymph node involvement, emphasizing the need for further prospective studies to validate and expand upon these observations.